Laser Osteotomy and Optical Sensing for Advanced Robotic Joint Tissue Surgery - Gunaratne, Gorokgodage Don Rajitha (Curtin University, 2021)
As part of an industry supported project on robotics for orthopaedic surgery, we investigated new tools for robotic orthopaedics including, lasers for bone cutting, diffuse reflectance spectroscopy (DRS) and autofluorescence spectroscopy (AFS) of animal and human joint tissue. The DRS and AFS work had the aim of creating a sensing system which could be used in laser surgery to differentiate joint tissue.